The Thermophilic Bacterial Growth Curve - Irdawati Irdawati; Ilsa Septia Putri; Syamsuardi Syamsuardi; Anthoni Agustien; Yetria Rilda (Bioscience, 2018)
Thermophilic bacteria are bacteria that can produce thermostable enzymes and used in various industries. Thermostable enzymes that can be produced by thermophilic microorganisms one of them is xylanase enzyme. Xylanase produced by microbes has optimum temperature characteristics and more diverse optimum pH on various substrates, which will affect the activity of the resulting xylanase enzyme. The influence of temperature greatly determines the activity of the enzyme at the time of catalyzing a reaction. At optimum pH conditions, the enzyme has an active side conformation that is substrate-like so that it can form a complex of appropriate enzymes and produce the product to its full potential. One of the thermophilic bacterial habitats of hot springs in West Sumatera is the Aro Sapan River hot spring located in Koto Parik Gadang Subdistrict in Ateh, South Solok District. The Saw Aro River hot spring has a temperature of 75 ° C and is pH 8 or alkaline. The aim to this research was to know the profile of the growth of thermophilic bacteria. This research is a descriptive method. The data obtained were analyzed descriptively. The conclusion is the best activity of xylanase thermophilic bacteria was at the sixth time incubation.